An exploratory study of clinical measures associated with subsyndromal pathological gambling in patients with binge eating disorder. - Yip, S; White, M; Grilo, C; Potenza, M (2011)
Both binge eating disorder (BED) and pathological gambling (PG) are characterized by impairments in impulse control. Subsyndromal levels of PG have been associated with measures of adverse health. The nature and significance of PG features in individuals with BED is unknown. Ninety-four patients with BED (28 men and 66 women) were classified by gambling group based on inclusionary criteria for Diagnostic and Statistical Manual-IV (DSM-IV) PG and compared on a range of behavioral, psychological and eating disorder (ED) psychopathology variables. One individual (1.1% of the sample) met criteria for PG, although 18.7% of patients with BED displayed one or more DSM-IV criteria for PG, hereafter referred to as problem gambling features. Men were more likely than women to have problem gambling features. BED patients with problem gambling features were distinguished by lower self-esteem and greater substance problem use. After controlling for gender, findings of reduced self-esteem and increased substance problem use among patients with problem gambling features remained significant. In patients with BED, problem gambling features are associated with a number of heightened clinical problems.